Asthma. Issue 843 (January 1996) - Calverley, P. M.
Abstract : Bronchial asthma is now recognised to be a major cause of morbidity and even mortality in people of all ages. Two important ideas have changed our approach to asthma management. The first is understanding that asthma is a chronic inflammatory disorder which needs regular treatment with anti-inflammatory drugs such as inhaled corticosteroids to prevent further attacks. The second development is the availability of prescribable peak flow meters, which allows both confident diagnosis and early prediction of relapse. Asthma management guidelines provide a logical treatment framework for most patients, but a few difficult cases still consume large amounts of medical time. The commonest problem is one of compliance with treatment which may respond to patient education, although this is not universally so. Other problems include misdiagnosis, acid reflux and, rarely, true corticosteroid-resistant asthma. Several potentially important new treatments have been developed. These include longer acting anticholinergic drugs, drugs with bronchodilator and some anti-inflammatory properties which antagonise or inhibit the production of leukotrienes, sub-types of phosphodiesterase inhibitor with anti-inflammatory properties and immunosuppressive drugs such as cyclosporin. Ultimately these new treatments must be rigorously tested and integrated into a care plan that remains centred on patient education.